A Comparison of the Transplant Efficiency between Intraportal and Intrasplenic Procedures in Hepatocyte Transplantation. (July 2018) - Ogasawara, Hiroyuki; Inagaki, Akiko; Imura, Takehiro; Saito, Yoshikatsu; Matsumura, Muneyuki; Fukuoka, Kengo; Fathi, Ibrahim; Miyagi, Shigehito; Ohashi, Kazuo; Unno, Michiaki; Kamei, Takashi; Satomi, Susumu; et al.
Abstract : Background: In hepatocyte transplantation, intraportal injection is regarded as the current standard procedure worldwide. However, there have been some reports that an intrasplenic approach is more efficient in terms of the engraftment and function of hepatocytes. Of particular interest, in pancreatic islet transplantation, which shares many aspects with hepatocyte transplantation, an intrasplenic method was recently proven to be superior to the intraportal method regarding islet engraftment. Therefore, in the present study, we compared the transplant efficiency between intraportal and intrasplenic approaches in hepatocyte transplantation. Methods: Rat hepatocytes were isolated using a modified two-step collagenase perfusion technique and then purified by Percoll density gradient centrifugation. Hepatocytes (1.0 × 10 7 ) with a viability exceeding 90% were directly injected into the portal vein (n=8) or spleen pulp (n=8) of analbuminemic rats using a gastight syringe for 60 seconds. Blood samples were taken pre-transplantation and at weeks 2, 4, 6, 8, 10, 12, and 16 after transplantation. The serum albumin levels were quantified using a rat albumin enzyme-linked immunosorbent assay kit. Results: The serum albumin levels of the intrasplenic group (pre-transplantation: 7.55±0.65 μg/ml, Week 2: 55.00±21.02 μg/ml, Week 4: 79.88±32.62 μg/ml, Week 6: 105.96±54.46 μg/ml, Week 8: 114.73±58.34 μg/ml, Week 10: 116.11±56.33 μg/ml, Week 12: 122.76±60.85 μg/ml, and Week 16: 133.96±66.03 μg/ml, respectively) were significantly lower than those of the intraportal group (pre-transplantation: 8.26±0.79 μg/ml, Week 2: 100.43±38.48 μg/ml, Week 4: 159.24±58.04 μg/ml, Week 6: 181.31±68.61 μg/ml, Week 8: 185.66±71.44 μg/ml, Week 10: 188.96±74.46 μg/ml, Week 12: 190.73±73.91 μg/ml and Week 16: 191.70±78.06 μg/ml, respectively, P<0.0001). Conclusions: The present study clearly showed that the intraportal injection procedure is more efficient than the intrasplenic procedure for performing hepatocyte transplantation.